EVALUATION OF CONSERVATIVE VS SURGICAL MANAGEMENT OF ACUTE CHOLECYSTITIS - QURATULAIN, .; ZAHID , MA; MALAK, W; AHMAD, Y; ARIF , MA; RIAZ, MS (Biological and Clinical Sciences Research Journal, 2024)
Cholecystectomy on an emergency basis or being treated with antibiotics gives a success rate of up to 86%. Objectives: The primary purpose of the study is to compare conservative vs surgical management of acute cholecystitis. Methods: This comparative observational study was conducted at Gondal Hospital Lahore from January 2024 to March 2024. Data were collected from 210 patients from different age groups. Patients with a clinical and imaging-confirmed diagnosis of acute cholecystitis were included in the study. Data were gathered on demographics, clinical presentation, laboratory results, imaging findings, treatment specifics, and patient outcomes. Variables included age, gender, symptom duration, white blood cell count, C-reactive protein levels, imaging results, treatment type, hospital stay duration, complications, and recurrence rates. Results: Data were collected from 210 patients. The mean age was similar between groups (54.23±2.35 years for conservative vs. 56.01±2.51 years for surgical). Gender distribution was comparable, with 54.3% males and 45.7% females in the conservative group and 50.5% males and 49.5% females in the surgical group. The complication rates were higher in the conservative management group (14.3%) compared to the surgical management group (7.6%). Specific complications in the conservative group included perforation (3.8%), abscess formation (5.7%), and sepsis (4.8%), whereas the surgical group experienced wound infections (2.9%), bile duct injuries (1.9%), and postoperative bleeding (2.9%). Conclusion: It is concluded that surgical management of acute cholecystitis, mainly through cholecystectomy, offers superior outcomes compared to conservative management. Patients undergoing surgery experience higher symptom resolution rates, shorter hospital stays, lower recurrence rates, and fewer complications.